Affordability and Subsidies in Public Urban Transport: What Do We Mean, What Can Be Done? - Serebrisky, T.; Gomez-Lobo, A.; Estupinan, N.; Munoz-Raskin, R. (2012)
Subsidy policies on public urban transport have been adopted ubiquitously. Both in developed and developing countries, subsidies are implemented under two major premises: (1) to increase public transport use and to reduce externalities, such as greenhouse gas emissions and congestion, and (2) to make transport more affordable, particularly for the poorest. This paper focuses on the latter. Despite the widespread implementation of subsidies, there are virtually no quantitative assessments of their distributional incidence, making it impossible to determine if these policy instruments are pro-poor. Using different tools to quantitatively evaluate the incidence and distributive impacts of subsidy policy options, this paper analyses the findings of a series of research papers that have studied urban public transport subsidy policies in developed and developing countries. Available evidence indicates that current public urban transport subsidy policies do not make the poorest better off. Supply side subsidies-provided to the operator-are, for the most part, neutral or regressive; while demand side subsidies-provided to the user-perform better, although many of them do not improve income distribution. Considering that the vast majority of developing countries justify public urban transport subsidies on social grounds, as a means to improve the mobility, and thus welfare, of the poorest, it is imperative to move away from supply side subsidies towards demand side subsidies and integrate transport social concerns into wider poverty alleviation efforts, which include the possibility of channelling subsidies through monetary transfer systems or through other welfare instruments (food subsidies, health services and education for the poor).